Altered ventricular mechanics after 60 min of high-intensity endurance exercise: Insights from exercise speckle-tracking echocardiography - Stewart, G.; Yamada, A.; Haseler, Luke; Kavanagh, J.; Koerbin, G.; Chan, J.; Sabapathy, S. (American Physiological Society, 2015)
© 2015 the American Physiological Society. Transient reductions in myocardial strain coupled with cardiac-specific biomarker release have been reported after prolonged exercise ( > 180 min). However, it is unknown if 1) shorter-duration exercise (60 min) can perturb cardiac function or 2) if exercise-induced reductions in strain are masked by hemodynamic changes that are associated with passive recovery from exercise. Left ventricular (LV) and right ventricular global longitudinal strain (GLS), LV torsion, and high-sensitivity cardiac troponin T were measured in 15 competitive cyclists (age: 28 ± 3 yr, peak O 2 uptake: 4.8 ± 0.6 l/min) before and after a 60-min high-intensity cycling race intervention (CRIT 60 ). At both time points (pre- and post-CRIT 60 ), strain and torsion were assessed at rest and during a standardized low-intensity exercise challenge (power output: 96 ± 8 W) in a semirecumbent position using echocardiography. During rest, hemodynamic conditions were different from pre- to post-CRIT 60 (mean arterial pressure: 96 ± 1 vs. 86 ± 2 mmHg, P < 0.001), and there were no changes in strain or torsion. In contrast, during the standardized low-intensity exercise challenge, hemodynamic conditions were unchanged from pre- to post-CRIT 60 (mean arterial pressure: 98 ± 1 vs. 97 ± 1 mmHg, not significant), but strain decreased (left ventricular GLS: -20.3 ± 0.5% vs. -18.5 ± 0.4%, P < 0.01; right ventricular GLS: -26.4 ± 1.6% vs. -22.4 ± 1.5%, P < 0.05), whereas LV torsion remained unchanged. Serum high-sensitivity cardiac troponin T increased by 345% after the CRIT 60 (6.0 ± 0.6 vs. 20.7 ± 6.9 ng/l, P < 0.05). This study demonstrates that exercise-induced functional and biochemical cardiac perturbations are not confined to ultraendurance sporting events and transpire during exercise that is typical of day-to-day training undertaken by endurance athletes. The clinical significance of cumulative exposure to endurance exercise warrants further study.